Diarrhea caused possibly by deficiency of sugar splitting enzymes - Bilir, Şule (The Turkish Journal of Pediatrics, 1972)
In this study, a chronic case of diarrhea was presented in a three and half year old boy, caused possibly by deficiency of sugar-splitting enzymes. Diagnosis of the intestinal disaccharidase deficiency was reached with the help of indirect methods. Definite improvements were observed in the patient following the reduction of the amount of foods rich in sucrose and starch.